2020
DOI: 10.37265/japiv.v12i2.126
|View full text |Cite
|
Sign up to set email alerts
|

Success Factors for Project Risk Management in Construction Projects: A Vietnam Case Study

Abstract: Despite being one of the oldest industries in human history, the modern construction industry is still suffering from delays, cost overruns, and low satisfaction levels. As construction activities greatly contribute to economic growth for any nation, the study of how to achieve success in construction projects should be continuously developing and attracting scholars’ attention. The Vietnam Construction Industry (VCI) is no exception. The economy in Vietnam has been growing fast and steady with significant con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Based on questionnaire responses and semi-structured interviews with project managers, the following political risks were identified: bureaucracy, corruption, and the possibility of project suspension. Intriguingly, these findings were also consistent with those of Le (2020) [24], who examined political risks in Vietnam. When asked if a project has ever been suspended owing to political concerns, A1 said that project B1 was completed and ready for handover but had been stalled for over three years because newly elected administrators refused to support the project due to its ties to the opposition.…”
Section: Qualitative Risk Response Framework Developmentsupporting
confidence: 87%
See 1 more Smart Citation
“…Based on questionnaire responses and semi-structured interviews with project managers, the following political risks were identified: bureaucracy, corruption, and the possibility of project suspension. Intriguingly, these findings were also consistent with those of Le (2020) [24], who examined political risks in Vietnam. When asked if a project has ever been suspended owing to political concerns, A1 said that project B1 was completed and ready for handover but had been stalled for over three years because newly elected administrators refused to support the project due to its ties to the opposition.…”
Section: Qualitative Risk Response Framework Developmentsupporting
confidence: 87%
“…Previous studies in construction revealed that the unstable cash flow is the most significant factor that leads to a project's delay followed by late payment [18][19][20][21][22][23]. One of the crucial project success criteria in the construction industry can be considered to be efficient and effective payments as per the related work [24][25][26]. Unlike other industries, timely completion of the construction projects is significantly affected by the delayed payments [27][28][29].…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…If the project is within the defined tolerance levels of these three factor, then the project is of high quality (Wu et al, 2018). Le et al (2020) indicated risk significantly negatively affects PI, SS, and time. Risks affect a project's performance; risks must be effectively controlled, monitored, and addressed to guarantee successful completion.…”
Section: Project Risks and Housing Project Successmentioning
confidence: 99%
“…Cash flow volatility has therefore been shown to reduce contractor profitability and lead to cost overruns in all aspects of the contractor's operations [65]. Timely payment for work completed in accordance with the associated works can be considered as one of the key criteria for a successful construction project [66]. If the contractor does not receive payment for the work carried out, they are unable to pay material suppliers, thus the supply of materials to the construction project is disrupted [67].…”
mentioning
confidence: 99%